x → ∞ lim ∑ n = 1 x F n 2 ∑ n = 1 x F 2 n − 1 = c a − b
The equation above holds true for positive integers a , b , and c , where b is square-free. What is a + b + c ?
Notation: F n denotes the n th Fibonacci number , where F 1 = F 2 = 1 and F n = F n − 1 + F n − 2 for n ≥ 3 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Another way to get that limit is to use the asymptotic from Binet's formula: F k ∼ 5 ϕ k .
A fairly non rigorous way would be to note that:
If lim x → ∞ ∑ n = 1 x g ( n ) ∑ n = 1 x f ( n ) = k , then lim x → ∞ g ( x ) f ( x ) = k .
lim x → ∞ F n 2 F 2 n − 1 = 5 ϕ 2 n 5 ϕ 2 n − 1 = ϕ − 1 × 5 = 2 5 − 5
L = n → ∞ lim ∑ k = 1 n F k 2 ∑ k = 1 n F 2 k − 1 = n → ∞ lim F n F n + 1 F 2 n = n → ∞ lim ( φ n + φ − n ) ( φ n + 1 − φ − n − 1 ) 5 ( φ 2 n − φ − 2 n ) = φ 5 = 5 + 1 2 5 = 2 5 − 5 Note that k = 1 ∑ n F 2 k − 1 = F 2 n and k = 1 ∑ n F k 2 = F n F n + 1 Binet’s formula: F n = 5 φ n − ( − φ ) − n
Therefore, a + b + c = 5 + 5 + 2 = 1 2 .
Problem Loading...
Note Loading...
Set Loading...
It can be easily proved geometrically that n = 1 ∑ x F 2 n − 1 = F 2 x
It can also be proved geometrically that n = 1 ∑ x ( F n 2 ) = F x F x + 1
This leaves us with the equation x → ∞ lim F x F x + 1 F 2 x
By d'Ocagne's identity, we know that F 2 x = F x ( F x − 1 + F x + 1 ) leaving us with the equation F x F x + 1 F x ( F x − 1 + F x + 1 )
This simplifies to 1 + F x + 1 F x − 1 .
As x → ∞ , The fraction becomes 1 + ϕ 2 1 .
ϕ = 2 5 + 1 and therefore 1 + ϕ 2 1 simplifies to 2 5 − 5 .
Therefore a + b + c = 1 2